Analisis Faktor-Faktor yang Mempengaruhi Keinginan Berpindah Auditor pada Kantor Akuntan Publik di Jawa Tengah dan Daerah Istimewa Yogyakarta - Permatasari, Devi (Jurnal Ilmiah Aset, 2012)
The purpose of this research was to investigate the factors of auditor’s turnover intention at public accountant firms. This research aimed to determine the effect of these factors, there were leadership style, role conflict, role ambiguity, promotion opportunities, pay satisfaction, personal growth needs, organizational commitment, and job satisfaction to auditor’s turnover intention from public accountant firms. Population of the research was all of auditors who have been working at public accountant firms in Central Java and DIY. Whereas the samples were 127 respondents who have been working as auditors at public accountant firms, spread in Central Java and DIY, there are Semarang, Surakarta, Purwokerto, and Yogyakarta. The hypothesis test was done by regression analysis using multivariate techniques Structural Equation Modeling (SEM) from software AMOS 16.0. Based on the results of hypothesis test, then the conclusions are auditor’s turnover intention from public accountant firms heavily influenced by factors, such as leadership style, role conflict, role ambiguity, promotion opportunities, paysatisfaction, and personal growth needs, through intermediaries organizational commitment and job satisfaction.